2011
DOI: 10.1055/s-0031-1284397
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Swimming Exercise Related Kidney Injury in Rats – Protective Effects of Acetylbritannilactone

Abstract: The aim of this study was to investigate the protective effects of acetylbritannilactone (ABL) on renal injury induced by acute exhaustive exercise in the rat. The exhaustive exercise induced kidney injury in rats was established by exhaustive swimming (ES). ABL (26 mg/kg) or polyglycol (control) were administrated orally by gastric gavage 24 h before training. Renal function, biochemical index, renal histopathological change, oxidative stress indices, renal cell apoptosis and inflammatory molecules were check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…Some reports showed that ABL is widely used for treatments of cancers [39][40] and oxidative stress-related human diseases [41]. Only one report referred to the protective effects of ABL on exhaustive swimming exercise causing AKI [22]. In our study, we found that the pretreatment of ABL on IOP-injected mouse partially restored kidney function.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Some reports showed that ABL is widely used for treatments of cancers [39][40] and oxidative stress-related human diseases [41]. Only one report referred to the protective effects of ABL on exhaustive swimming exercise causing AKI [22]. In our study, we found that the pretreatment of ABL on IOP-injected mouse partially restored kidney function.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have indicated that ABL has antioxidant, anti-inflammatory, and organ-protective activities in vivo and in vitro [20][21]. ABL prevented acute renal injury by inhibiting apoptosis and alleviating inflammation and oxidative stress in exhaustive swimming rats [22]. However, the effect of ABL on CI-AKI is unknown.…”
Section: Introductionmentioning
confidence: 96%
“…The study showed that there were more touches of the ball and attacking play in the smaller game formats ( Sampaio and Maças, 2012 ); there was a higher frequency among the variables for attacking play in all age groups and playing surfaces (goals, shots on goal and balls entering the penalty area) in the smaller-sided games (5v5 and 7v7) than in the 9v9 format ( Okihara et al, 2004 ). It should be noted in particular, that the U-9 age group playing in the 5v5 format created more attacking moves and attacks than any other age group and game format, directly influencing the intensity of play ( Koklu et al, 2011 ) and therefore, the learning process during training ( Iaia et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will increase the oxygen consumption of cardiomyocytes, which may produce an imbalance between reactive oxygen species (ROS) and antioxidants, inducing oxidative stress as a result of increased ROS production [13] and damage to cardiac structure, metabolism, and function [4, 5]. More specifically, oxidative stress is the imbalance between oxidation and antioxidation system.…”
Section: Introductionmentioning
confidence: 99%